Asuhan Keperawatan Jiwa Pada Pasien Dengan Risiko Perilaku Kekerasan di Wisma Nuri RSJ Prof. HB. Saanin Padang - Defri Fairuz Zaki; Ramaita Ramaita; Vivi Yuderna; Dwi Happy Anggia Sari (CV. ITTC INDONESIA, 2026)
Risk of violent behavior is a condition in which individuals have the potential to harm themselves, others, or the environment physically and psychologically. This condition is commonly found in patients with mental disorders, especially schizophrenia, and requires appropriate psychiatric nursing care. This study aimed to implement psychiatric nursing care for patients at risk of violent behavior at Wisma Nuri Prof. HB. Saanin Psychiatric Hospital Padang. The research method used was a case study with a nursing process approach including assessment, diagnosis, intervention, implementation, and evaluation. The assessment results showed that the patient experienced labile emotions, irritability, sharp gaze, high-tone speech, and aggressive behavior. The main nursing diagnosis established was risk of violent behavior with a secondary diagnosis of self-care deficit. Interventions were carried out through implementation strategies including deep breathing exercises and hitting pillows, medication adherence, adaptive verbal communication, and spiritual approaches. After nursing care was implemented, the patient was able to control emotions and reduce aggressive behavior independently. The implementation strategy proved effective in helping patients control the risk of violent behavior and improve self-care abilities.